(3GQJjGM GdCcHGO HCQHGM abO GdChdGOs - (3GdSNGhj , TeS GdOjf eMeO Hf YHO GdQMef Hf eMeO GdSNGhj, GdSNGhj,J (B902 (3g` s
(3ChdgG (B:s
(3hHYO adeG cGf GdehJ gh GdMGOK GdYXje s
(3BNQgG (B:s
(3jSQ Gddg dcd efG Edi GdNjQGJ GdCSHGH NJe Gddg dgeG HGdNjQ hdLejY GdeSdejf s
(3GdfSNI HgG MhGTs
(3fSNI QGHYIs
(3hbO Cdag GdeDda aj QeVGf SfI (B864 (3g` hgh eTJed Ydi ebOeI hNeSI CHhGH hNGJeIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs